2019
DOI: 10.1088/1361-6471/ab3698
|View full text |Cite
|
Sign up to set email alerts
|

First observation of high-spin states in the N = 83 nucleus 142Pr

Abstract: High-spin states of the N = 83 nucleus 142Pr have been observed for the first time using the 138Ba(7Li, 3n) reaction at a beam energy of 38 MeV. A total of 40 new transitions and 22 new levels have been identified, leading to a considerable extension of the level scheme of 142Pr. The experimental level structures of 142Pr are compared with its neighboring N = 83 isotones 144Pm and 146Eu. Shell model calculations employing the jj56pna interaction reproduce the experimental findings and provide guidance in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…As depicted by Figure , the H of ttz GC or tth GC is only localized on the ttz G or tth G component, and it resembles the H of ttz G or tth G. However, the L and L + 1 are delocalized on the whole base pairs and they could be seen as combinations of the LUMOs of ttz G (or tth G) and C. Therefore, the lowest electronic transitions of ttz GC and tth GC have partial CT character, which is different from those of ttz AU and tth AU. The delocalization of the L and L + 1 MOs of ttz GC and tth GC implies that the transverse electronic communication is strong between two base moieties, which indicate that ttz G and tth G could exhibit a positive effect on charge migration along duplex DNA/RNA. By examining the transition energies shown in Table , one can find that the transition energies obtained by the TD‐CAM‐B3LYP method are about 0.4 eV larger than those from TD‐B3LYP, which is attributed to the higher HF exchange percentage in the CAM‐B3LYP functional.…”
Section: Resultsmentioning
confidence: 99%
“…As depicted by Figure , the H of ttz GC or tth GC is only localized on the ttz G or tth G component, and it resembles the H of ttz G or tth G. However, the L and L + 1 are delocalized on the whole base pairs and they could be seen as combinations of the LUMOs of ttz G (or tth G) and C. Therefore, the lowest electronic transitions of ttz GC and tth GC have partial CT character, which is different from those of ttz AU and tth AU. The delocalization of the L and L + 1 MOs of ttz GC and tth GC implies that the transverse electronic communication is strong between two base moieties, which indicate that ttz G and tth G could exhibit a positive effect on charge migration along duplex DNA/RNA. By examining the transition energies shown in Table , one can find that the transition energies obtained by the TD‐CAM‐B3LYP method are about 0.4 eV larger than those from TD‐B3LYP, which is attributed to the higher HF exchange percentage in the CAM‐B3LYP functional.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that virus infection may change the miRNA cell repertoire expression (Park et al, 2017;Chirayil et al, 2018;Del Mar Dıáz-Gonzaĺez et al, 2019), and that miRNA may also regulate gene expression at the transcriptional level (Lytle et al, 2007;Ørom et al, 2008;Place et al, 2008;Zhang et al, 2014), we conducted a bioinformatics analysis to predict miRNA interaction with the PDCD1 -606G>A polymorphic site. Three miRNAs were predicted to bind to the mutant A allele: i) the hsa-MiR-6798-5p up-regulates decidual NK cells in recurrent spontaneous abortion (Sfera et al, 2015), ii) the hsa-MiR-6775 is reported to silence the transcription of the alpha 7-cholinergic nicotinic receptor gene (CHRNA7) expressed on lymphocyte surface and associated with lymphocyte anergy, T regulatory cell differentiation and immunologic tolerance, which consequently may predispose to cancer development (Li et al, 2018), and iii) the hsa-MiR-4776-5p specifically targets the nuclear factor Kappa B inhibitor beta (NFKBIB) mRNA in Influenza A virus-infected cells, leading to activation of NF-kB, and survival of infected cells (Othumpangat et al, 2017). The hsa-MiR-6771-5p binds to the -606 G alleles with high affinity (e-value = 1.1) and weakly to the mutant A allele (e-value = 6.2), and it is involved in ZIKA-associated microcephaly.…”
Section: A B C D E Fmentioning
confidence: 99%